2020
DOI: 10.1021/acs.joc.0c00186
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cross-Conjugated Polyenes via Palladium-Catalyzed Oxidative C–C Bond Forming Cascade Reactions of Allenes

Abstract: An efficient palladium-catalyzed oxidative C−C bond forming cascade reaction of allenes involving a coupling between an enallene and an allenyne followed by a carbocyclization of the generated Pd-intermediate was developed. This cascade reaction afforded functionalized cross-conjugated polyenes. The enallene is initially activated by palladium and reacts with the allenyne to give the crossconjugated polyenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Similar to carbo­(oxa)­cyclization-alkynylation of enallenes with alkynes, the coupling of allenyne ( 52a ) was also investigated by Naidu and Bäckvall, using allene-tethered alkyne ( 52b ) as the coupling partner (Scheme ). Various cross-conjugated polyenes ( 52c ) were fabricated under the previously employed oxidative conditions by adding 20 mol % Na 2 CO 3 as an additive. Aerobic biomimetic oxidative conditions were also suitable for reducing the amount of oxidant required for this transformation.…”
Section: Aa Coupling In Constructing Cyclic C-skeletonsmentioning
confidence: 99%
“…Similar to carbo­(oxa)­cyclization-alkynylation of enallenes with alkynes, the coupling of allenyne ( 52a ) was also investigated by Naidu and Bäckvall, using allene-tethered alkyne ( 52b ) as the coupling partner (Scheme ). Various cross-conjugated polyenes ( 52c ) were fabricated under the previously employed oxidative conditions by adding 20 mol % Na 2 CO 3 as an additive. Aerobic biomimetic oxidative conditions were also suitable for reducing the amount of oxidant required for this transformation.…”
Section: Aa Coupling In Constructing Cyclic C-skeletonsmentioning
confidence: 99%
“…[ 27 ] Recently, Naidu and Bäckvall developed an efficient oxidative annulation reaction for the synthesis of functionalized polyenes between yne‐allenes 7 and enallenes 8 (Scheme 3a). [ 28 ] This palladium‐catalyzed intermolecular carbocyclization cascade in CH 3 CN at 80°C provides a wide variety of interesting polyene products 9 in high yield (up to 90%) and with excellent regio‐ and stereoselectivities by using 1,4‐benzoquinone (BQ) as the oxidant. The reaction also tolerated aerobic conditions with catalytic amount of BQ together with Co(salophen).…”
Section: Synthesis Of Carbocyclesmentioning
confidence: 99%
“…In the palladium-catalyzed allylic C–H oxidation reaction, early studies on cyclic or acyclic alkenes by the group of Åkermark, Bäckvall, White, and Shi showed that the reactions proceed via π-allylpalladium­(II) intermediates generated through allylic C–H bond cleavage. However, reports on the dendralene synthesis involving C–H bond cleavage are scarce . In particular, we were inspired by Bäckvall and co-workers who reported a straightforward synthesis of [3]­dendralene derivatives through palladium-catalyzed allenic C–H bond oxidation (Scheme d) .…”
mentioning
confidence: 99%